Economics of site specific crop density in precision sunflower (Helianthus annuus L.) production - Monoki, Szabolcs; Csornai, Gabor; Zalai, Mihaly; Nagy, Janos (Acta Agraria Debreceniensis, 2023)
In this research, the crop density of sunflower was examined, which, thanks to the tools available for precision crop production and knowledge of the market environment of sunflower production, best fits the heterogeneous areas of the given production zones and meets the economic requirements. These components together directly influence the effectiveness of sunflower production. In the year of 2021 and 2022, we carried out a site-specific crop density sunflower experiment in two fields with the same soil type, by sowing significantly different amounts of seeds within the given zones. We have established that the sunflower, although a plant with excellent adaptability, reacts sensitively to the place of production and the effect of the year, in zones with heterogeneous productivity, and shows a reaction to sowing with a variable number of seeds per zone, even when examined based on economic aspects.